Software User Interface and Algorithm Development for Signal and Noise Characterization - Phoong, Wei Siang (2015)
Atomic force microscopy (AFM) also known as “Scanning force microscopy (SFM)” is high resolution scanning probe. The resolution of scanning object is reached to the order of fractions of a nanometer. Its advantage is the performance of AFM is better than optical diffraction. The wide application range of AFM include mapping, measuring or scaling in nanometer scale precise state. To construct an AFM, Optical Beam Deflection (OBD) system was always applied. Laser as source to emit light and photodiode as detector to detect the light. The cantilever is scan the object along X-axis direction and Y-axis direction. The light is emit to cantilever and reflect the light to photodiode. The data from photodiode is read by LabVIEW software for further develop to obtain useful output data. The previous task done by senior is I/V converter and algorithm for detect location of photodiode are implement by using LM741 op-amp chip on printed circuit board. The output data display in array is only x-axis direction. In my final year project, the purpose of project is reconstruct the I/V converter by using op-amp chip other than LM741 and the algorithm for detect location of photodiode is implement by LabVIEW software. The output data display in array is implement to display in two dimension array with X-axis direction and Yaxis direction.